1973
DOI: 10.1021/bi00748a028
|View full text |Cite
|
Sign up to set email alerts
|

Shape and volume of anti-poly-D-alanyl antibodies in the presence and absence of tetra-D-alanine as followed by small-angle x-ray scattering

Abstract: The conformation of two anti-poly(D-alanyl) antibodies was studied by small-angle X-ray scattering before and after interaction with hapten. With both samples a volume contraction could be observed upon interaction with the tetra-D-alanine hapten. The anti-poly@-alanyl) antibodies obtained by immunization with poly@-alanyl) diphtheria toxoid showed a decrease of the volume by 10% and a decrease of the radius of gyration by 7.7% when 90% of the binding sites were occupied by hapten. With anti-poly@-alanyl) huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…The use of three NaCl concentrations examined potential electrostatic effects on the IgG1 structure, whereas heavy water is a known promoter of protein self-association. By comparison, earlier scattering studies on human IgG1 reported few scattering and ultracentrifugation runs or were performed in nonphysiological buffer conditions (28,38,39,(47)(48)(49). Both IgG1 6a and IgG1 19a showed similar experimental R g and R xs values and the same overall length of 16 nm ( Table 1 6.3-6.4 S, which were indistinguishable within error.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The use of three NaCl concentrations examined potential electrostatic effects on the IgG1 structure, whereas heavy water is a known promoter of protein self-association. By comparison, earlier scattering studies on human IgG1 reported few scattering and ultracentrifugation runs or were performed in nonphysiological buffer conditions (28,38,39,(47)(48)(49). Both IgG1 6a and IgG1 19a showed similar experimental R g and R xs values and the same overall length of 16 nm ( Table 1 6.3-6.4 S, which were indistinguishable within error.…”
Section: Discussionmentioning
confidence: 74%
“…The cross-sectional plot for immunoglobulins exhibits two distinct regions, a steeper innermost one and a flatter outermost one (28) (10). IgG1 b12 has high sequence identity to IgG1 6a and IgG1 19a (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…X-ray small-angle scattering data of Pilz and co-workers [4,5] indicate a decrease in R, of rabbit anti-poly(D-alanyl) and anti-azophenyl-lactoside antibodies after their complexing with tetra-D-alanylamide and p-azophenyl-/3-lactoside haptens, respectively. The changes in R, observed, namely 7.1% in the case of anti-polyalanyl antibodies (90% of binding sites occupied) and 2.5% in the case of anti-azophenyllactoside antibodies (60% of binding sites occupied) compare well with values obtained in the present study, that is, 4.6% for the early antibody and 7.5% for the late antibody.…”
Section: Resultsmentioning
confidence: 98%
“…The 30S ribosomal subunit of Escherichia coli is comprised of 21 ribosomal proteins and one 16S rRNA molecule. Substantial information about the primary structure of these components has accumulated during the last several years (reviewed in refs.…”
mentioning
confidence: 99%